Pengaruh Perilaku Islami Terhadap Kondisi Emosi Positif Remaja Yang Tinggal Di Lapas Kutoarjo Jawa Tengah - Diponegoro, Ahmad Muhammad (Journal of Educational, Health and Community Psychology, 2012)
AbstractÂ A number of researchers have found that adolescents who score high on measures of spirituality or religiosity are less likely than their peers to engage in violent or other antisocial behaviour. This research explores selected spiritual factors (Islamic behavior) that research has indicated may play an important protective role in strengthening resilience in young people and minimizing at-risk behavior that may be associated with school violence in Indonesia. Islamic behavior and manners are supposed to be derived from the Quran and sunnah. In this research, we review the professional literature regarding selected Islamic tenet as they pertain to adolescents and at-risk behavior and consider these factors might be useful in the prevention of youth violence in Indonesia. We use these factors to treat the adolescents from, who were sentenced more than 3 months in Kutoarjo adolescentsâ prison. The subjects were 30 adolescents who were approximately at the same age. Result: there was the important role of Islamic behavior toward youth emotion in prison. Key words: Islamic behavior, emotion, juvenile prisonÂ